2011
DOI: 10.1001/archgenpsychiatry.2011.32
|View full text |Cite
|
Sign up to set email alerts
|

Neural Correlates of Food Addiction

Abstract: Context Research has implicated an addictive process in the development and maintenance of obesity. Although parallels in neural functioning between obesity and substance dependence have been found, no studies have examined the neural correlates of addictive-like eating behavior. Objective To test the hypothesis that elevated “food addiction” scores are associated with similar patterns of neural activation as substance dependence. Design Between-Subjects fMRI study. Participants Forty-eight healthy adole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
408
5
11

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 598 publications
(447 citation statements)
references
References 75 publications
17
408
5
11
Order By: Relevance
“…In keeping with the idea that Orexin-1 receptor mechanisms in binge eating in rats L Piccoli et al neural systems that motivate and reinforce drug abuse may also underlie behaviors associated with food seeking and intake (Gearhardt et al, 2011b), this study investigated the ability of OXR antagonist to block BE episodes and to evaluate the involvement of OX 1 and OX 2 mechanisms in the control of BE episodes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In keeping with the idea that Orexin-1 receptor mechanisms in binge eating in rats L Piccoli et al neural systems that motivate and reinforce drug abuse may also underlie behaviors associated with food seeking and intake (Gearhardt et al, 2011b), this study investigated the ability of OXR antagonist to block BE episodes and to evaluate the involvement of OX 1 and OX 2 mechanisms in the control of BE episodes.…”
Section: Discussionmentioning
confidence: 99%
“…Neural systems that motivate and reinforce drug abuse have also been proposed to underlie behaviors associated with compulsive food seeking and food intake (Johnson and Kenny, 2010;Hoebel, 1985;Volkow and Wise, 2005;Corwin et al, 2011;Gearhardt et al, 2011b;Wang et al, 2011). These findings raise the question of whether the OX system may also have a role in eating disorders characterized by compulsive binge-type episodes, such as bulimia nervosa and BED.…”
Section: Introductionmentioning
confidence: 99%
“…the tendency for restraint to break down when confronted by emotional or external cues to eat) has been associated with lesser pre-meal ACC responses to visual food versus non-food cues , and scores on food addiction (i.e. a pattern of compulsive eating typifi ed by tolerance, withdrawal and loss of control) have been associated with greater medial orbitofrontal cortex (OFC), amygdala and ACC responses to anticipated receipt of a milkshake, and lesser activation in the lateral OFC in response to actual receipt (Gearhardt et al, 2011).…”
Section: Neuroimaging Studies Of Obesity and Appetitive Traitsmentioning
confidence: 99%
“…22 For example, research has demonstrated diminished striatal dopamine release after eating desirable food, 23 and abnormalities in dopaminergic response to food cues and actual food consumption in adults with food addiction. 24 Diminished dopamine receptor-binding capacity in the hypothalamus, which controls satiety and hunger, has been observed in individuals with ADHD, 25 suggesting a direct causal link between ADHD and eating patterns, although research with children is limited. Hence, initial evidence suggests that dopaminergic dysfunction leads to impairment in reward processing that promote both obesity and ADHD.…”
Section: Introductionmentioning
confidence: 99%